Cultivation and description of Duncaniella dubosii sp. nov., Duncaniella freteri sp. nov. and emended description of the species Duncaniella muris. Issue 5 (6th April 2020) - Miyake, Sou; Ding, Yichen; Soh, Melissa; Low, Adrian; Seedorf, Henning
Abstract : Three bacterial strains, C9, H5 and TLL-A3, were isolated from fecal pellets of conventionally raised C57BL/6J mice. Analysis of 16S rRNA genes indicated that the strains belonged to the Muribaculaceae, and shared 91.6–99.9 % sequence identity with the recently described Duncaniella muris DSM 103720 T . Genome-sequencing of the isolates was performed to compare average nucleotide identities (ANI) between strains. The ANI analysis revealed that all isolates shared highest ANI with D. muris DSM 103720 T, with strain C9 being most similar (ANI: 98.0 %) followed by strains H5 (ANI: 76.4 %) and TLL-A3 (ANI: 74.4 %). Likewise, digital DNA–DNA hybridization (dDDH) indicated high similarity of strain C9 (dDDH: 86.6 %) to D. muris DSM 103720 T, but strains H5 and TLL-A3 showed lower similarity (dDDH <35 %) to either of the three type species of the Muribaculaceae ( Muribaculum intestinale DSM 28989 T, Paramuribaculum intestinale DSM 100749 T, D. muris DSM 103720 T ). MK-10 and MK-11 were abundant in all three isolates, but concentrations varied between species. Based on genotypic, phylogenetic and phenotypic differences, the strains TLL-A3 and H5 are considered to represent novel species of the genus Duncaniella, for which the names Duncaniella freteri sp. nov., and Duncaniella dubosii sp. nov., are proposed. The respective type strains are TLL-A3 T (=DSM 108168 T =KCTC 15769 T ), and H5 T (=DSM 107170 T =KCTC 15734 T ). Strain C9 reveals limited sequence dissimilarity and minor differences in morphological properties with Duncaniella muris DSM 103720 T and is therefore proposed to belong to the same species. The respective strain is C9 (=DSM 107165=KCTC 15733).